Evektifitas Pendidikan Maslahat Pra-Nikah dalam Mencegah Pernikahan Dini Bagi Remaja - Khoiri, Ahmad; Rosyiful Aqli, Mohamad; Rosyidatul Husnah, Cholis (LPPM Universitas Ekasakti Padang, 2024)
Efforts to prevent early marriage are not enough to be limited to legal regulations alone. It is necessary for various institutions, including religious institutions, to carry out activities as preventive steps to prevent early marriage. The government has attempted to prevent child marriage by revising the marriage law regarding the age limit for marriage for women and men, namely at least 19 years. This is a good step from the government in preventing child marriage. To support this, IPNU and IPPNU Jember Regency created an activity program in the form of Pre-Marriage Mashlahat Education. The target participants in this activity are teenagers in Jember district who are entering high school age and above. This aims to educate from an early age for awareness of the dangers of child marriage. Apart from that, pre-wedding maslahat education is also attended by prospective brides and grooms. To provide information regarding tips for forming a Sakinah, Mawaddah Warahman family. This research reviews the effectiveness of pre-marital maslahat education as an effort to prevent early marriage for teenagers. Primary data consists of interviews and observations carried out in the form of activities on 17 institutions spread across Jember Regency. The results of this research show that many factors result from early marriage, including education, economics, and religious understanding. So, with this pre-marital maslahah education activity, it is hoped that it will be a solution for children who refuse to be forced to marry early.